Semiótica para demonstração técnico-científica da verdade jurídico-tributária - Passos, Raphael Ricardo de Faro (2025)
The present doctoral thesis focuses (object) on the semiotics of evidence and technicalscientific proof in tax matters. Its objective is to establish the prominence of technicalscientific demonstration of legal-tax truth for resolving complex disputes (hard cases) that require clarification through evidence and technical-scientific proof admissible in tax law. The problem addressed concerns the inductively proven circumstance, derived from the language of judicial and administrative tax jurisprudence, that there is resistance among adjudicators to authorize technical-scientific demonstration in tax matters, even in complex disputes (hard cases). Frequently, early judgments are made, bypassing the necessary technical-scientific elucidation of the case. The justification for this scientific endeavor lies in the defended prominence of technicalscientific demonstration in tax law, particularly in events with legal-tax repercussions in the context of taxation. These events, objectively, for their correct understanding, necessarily depend on the borrowed expertise of technical scientists in relevant scientific fields, as applied by adjudicators. The core question arises from the inquiry: Is technical-scientific demonstration prominent or not in legal-tax disputes submitted for judicial resolution, especially when there is an objective dependency on technical-scientific knowledge? The hypothesis, therefore, posits that the integration of technical-scientific expertise by adjudicators should be prominent for the resolution of complex disputes (hard cases) in tax matters. The methodology, method, or, as preferred here, “methodetics” of research is firmly grounded in Aristotelian logic, predicate calculus, normative logic, and Charles Sanders Peirce’s theory of signs, presenting an abductive-deductive-inductive approach. The thesis ultimately concludes that adjudicators must prominently integrate the technicalscientific propositions provided by experts with their own legal-tax propositions, aiming to elucidate the legal-tax truth in complex disputes (hard cases) in the field of taxation